Improving the communicative competence of education managers by engagingthem in management training group work - Shalimova, I; Shalimova, A (Problems of Engineer-Pedagogical Education, 2019)
The article is devoted to the question of improving communicative competence of higher educational institution managers. The article defines psychological and pedagogical determinants of the development of communicative competence of a higher educational institution manager, and reveals the relationship between the level of communicative competence of the education manager and the peculiarities of his/her self-awareness, complexity and structure of criteria for evaluating other participants in the pedagogical process. It is established that there is a correlation between the level of formation of communicative competence of the head of an educational institution and the set of criteria for evaluating other participants in the educational and upbringing process. Psychological factors determining the development of communicative competence of an individual are revealed. The article finds that the important psychological factors that the development of communicative competence of higher educational institution managers depends on include completeness of perception and knowledge about their own personality, ability to adequately express their feelings and psycho-emotional states, etc. The article substantiates that one of the most effective methods of forming communicative competence of education managers is socio-psychological group training. It is proved that the main mechanism that provides the solution of the tasks of experimental training in the groups of managerial training is interpersonal feed back that the respondents give to their communication partners. The authors have theoretically substantiated, developed and partially tested the methodology of forming such a level of communicative competence of the heads of departments of higher medical educational institutions that meet the requirements of today's pedagogical practice. The paper emphasizes that the designed method for developing the productive level of communicative competence among the heads of departments of higher medical educational institutions can be applied in practical professional activities of heads of higher educational institutions of different types and forms of ownership.